Challenges and opportunities of global change for sustainability in Central America - Quesada Román, Adolfo (2025)
[Introduction]: Global change presents pressing challenges for Central America, including increasing hydrometeorological disasters, environmental pollution, and soil degradation. [Aims]: This study examines socio-environmental trends from 1990 to 2020 using comprehensive datasets from the World Bank and EMDAT. [Methodology]: Through country-specific correlation analyses, we uncover complex statistical relationships between socioeconomic and environmental variables. [Results]: The findings highlight critical interactions, such as the link between economic diversification away from agriculture and GDP growth, which is paradoxically accompanied by rising CO2 emissions. Renewable energy consumption emerges as a pivotal factor in mitigating carbon footprints, while sustainable freshwater management is shown to be essential for long-term economic resilience. [Conclusions]: These results offer valuable insights into the dynamics of economic growth, agricultural practices, and environmental sustainability in the region. By addressing these multifaceted challenges through coordinated and integrated strategies, Central America could enhance regional perspective and potential research gaps, safeguard its natural resources, and foster a sustainable and resilient future through international, regional and national institutions initiatives and projects.